MOTIVASIINDIVIDU BERGABUNG DALAM KOMUNITAS PENGGEMAR TIMSEPAKBOLA (STUDI KASUS: LIMA ANGGOTA FANSCLUBUNITED INDONESIA CHAPTER BALI) - Setiawan, I Made Nopa Beni; Arjawa, I Gusti Putu Bagus Suka; Astika, Ketut Sudhana (JURNAL ILMIAH SOSIOLOGI (SOROT), 2016)
ABSTRACT This essay is about the motivation of local Manchester United’s fans in joining UI Bali community. Manchester United is a European elite football team that has so many fans from around the world, including Indonesia. This research is using constructivism approach with social action theory to find out the motivation of UI Bali’s members. This research is a descriptive research using case study method. The data was gathered from interview and observation. The result is explanation about the categorization of behavioral motives of the UI Bali’s members. This was started with the exploration phase of the informants that was obtained from family, friends, and their surroundings, so that they are committed to be a fan of Manchester United. At least, informant’s motives are divided into two category, first early behavioral motive, and secondly, behavioral motive after the informants being a member of UI Bali. researcher found that informants early behavior are mostly based on value rationality, and the rest are based on affective rationality. Then, informants’ continuing motives after joining UI Bali are based on instrumental rationality behavior. This research also found that there are some impacts for the informants after joining this community, that the get some self-developments, such as the expansion of their friendship range, increase of organizational experience, culture uniformity, and love or loyalty to Manchester United are getting stronger. Key words: Manchester United, United Indonesia, motivation, rationality.